Low dose contraceptive pill containing gestoden or intrauterinal contraceptive device in perimenopausal women? Satisfaction, influence on endometrium and bleeding profile - Sobczuk, Anna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Selection of proper method of contraception for women in perimenopausal age is much more difficult than in young women. Introduction of oral hormonal contraception in premenopause like any other farmacological interference should be correlated with benefits-risks evaluation. Women who should not apply oral contraception (smokers, obese, with hypertension, with high risk of thrombosis or ischaemic disease) are recommended to use IUCD (intrauterinal contraceptive device). The aim of this study is a comparison of 2 contraceptive methods used by sexually active women in perimenopausal age with prolonged menorrhoea. Two groups were considered: women using low-dose oral contraceptive pill (OCP) and women using IUCD containing levonorgestrel. The safety, effectiveness and general satisfaction of both methods were evaluated judging: endometrium thickness, regularity, duration and intensity of menorrhoea; level of Hb, weight at the beginning of study and after 6 months and occurrence of undesired effects such as headaches, breast tenderness and tension or pain/ distention of the abdomen. 50 women participated in the study, 35 chose OCP containing gestoden, 15 preferred insertion of IUCD releasing levonorgestrel. Conclusion: employment of two-component hormonal contraceptive pill in perimenopausal women benefits the profile of menstruation and seems to be a safe method in non-smokers. IUCD with levonorgestrel can be applied as an alternative for it reduces intensity and duration of menorrhoea and is well tolerated by perimenopausal women.